Social policy and cognitive enhancement: lessons from chess - Mihailov, E; Savulescu, J (Springer Netherlands, 2018)
Should the development of pharmacological cognitive enhancers raise worries about doping in cognitively demanding activities? In this paper, we argue against using current evidence relating to enhancement to justify a ban on cognitive enhancers using the example of chess. It is a mistake to assume that enhanced cognitive functioning on psychometric testing is transferable to chess performance because cognitive expertise is highly complex and in large part not merely a function of the sum specific sub-processes. A deeper reason to doubt that pharmacological cognitive enhancers would be as significant in mind sports is the misleading parallel with physical enhancement. We will make the case that cognitive performance is less mechanical in nature than physical performance. We draw lessons from this case example of chess for the regulation of cognitive enhancement more generally in education and the professions. Premature regulation runs the risk of creating a detrimental culture of suspicion that ascribes unwarranted blame.